Histopathologic Analysis of Gastrointestinal Tract Polypoidal Lesions in a Tertiary Care Centre - Chalise, Sanat; Hirachan, Suspana; Pradhan, Sailesh (Journal of Institute of Medicine Nepal, 2024)
Introduction Gastrointestinal tract polyps lesions are commonly encountered lesions in histopathological examination. It is necessary to examine these polyps and to determine its nature for the management of patient. Methods A descriptive cross-sectional study was done in the Pathology Department of Kathmandu Medical College from January 2023 to July 2023 after obtaining ethical clearance. The study included all gastrointestinal tract polyps or polypoidal lesions identified endoscopically or colonoscopically, biopsied, and received for histopathological analysis. Results Among 96 polyps examined, 58 (60.4%) were seen in males and 38 (39.6%) were seen in female. The age of the patients ranged from 15 to 89 years, with a mean age of 45 years. Most of the polypoidal lesions were less than 1 cm in size (76 cases, 79.1%). Colon (54 cases, 56.2%) was the most common site followed by the stomach (22 cases, 23.0%). Of the polypoidal lesions, 66(68.8%) were non-neoplastic polyps, while 30(31.2%) were neoplastic. Tubular adenoma with low-grade dysplasia was the most common polyp identified in the colon (17 cases, 17.8%). Hyperplastic polyps were the most common type overall (19 cases, 19.8%), stomach being the most frequent site (13 cases, 13.6%). Conclusion A wide range of histological types of polypoidal lesions were found in the gastrointestinal tract. The most frequent occurrence was in the colon, and the majority were non-neoplastic in nature.